"Open-top" microfluidic device for in vitro three-dimensional capillary beds. Issue 20 (25th September 2017) - Oh, Soojung; Ryu, Hyunryul; Tahk, Dongha; Ko, Jihoon; Chung, Yoojin; Lee, Hae Kwang; Lee, Tae Ryong; Jeon, Noo Li
Abstract : We introduce a novel microfluidic device to co-culture a blood vessel network and cell tissues in an in vivo -like niche. Abstract : We introduce a novel microfluidic device to co-culture a blood vessel network and cell tissues in an in vivo -like niche. Our "open-top" microfluidic device is composed of microchannels with micropores in the ceiling, which provides direct fluid access from reservoir to microchannel. Fluid connections through micropores afford novel advantages, including: i) the long-term culture of large-scale microvessel network, ii) access of different fluids to inner and exterior sides of the microvessel, and iii) co-culturing of the microvessel network and small cell tissue. In this study, we have successfully assembled microvessels with 5 mm channel widths. We were also able to mimic capillary bed conditions by co-culturing microvessels with cancer spheroids. Intimate contact between the cancer spheroid and microvessel caused vessel recruitment and an increase in vessel formation, and affected vessel morphology. We expect this device to be used as a novel platform for vascularized tissue models.